Quercetin regulates autophagy and attenuates airway inflammation in a murine model of asthma: association with PI3K/Akt/mTOR signaling pathway modulation - Lang, Liye; Liu, Sheng; Zhang, Weishuai; Zhang, Jialin; Liu, Hua (Frontiers in Pharmacology, 2026)
BackgroundAs a natural flavonoid, quercetin has anti-inflammatory and anti-oxidative activities. Studies confirm its beneficial effect on asthma, but the underlying mechanism remains unclear. This study aimed to systematically evaluate quercetin’s efficacy in treating asthma, explore its regulatory role in asthma-related autophagy and associated signaling pathways, and provide new insights for asthma treatment research.MethodsIn vivo, ovalbumin (OVA)-induced asthma model mice were first successfully established, then randomly assigned to five groups: control, asthma model, low/high-dose quercetin, and dexamethasone positive control. ELISA, histopathological staining, immunohistochemistry and Western blot were used to assess quercetin’s therapeutic effect and molecular mechanism. To complement the in vivo findings from the OVA-induced asthmatic mouse model, in vitro experiments were conducted using the human bronchial epithelial cell line BEAS-2B. Specifically, the cell line was stimulated with TNF-α and IL-4 to establish an inflammatory model, further validating quercetin’s regulation of autophagy and inflammation.ResultsIn vivo, quercetin reduced inflammatory cell count and proinflammatory cytokine levels in asthmatic mice’s bronchoalveolar lavage fluid (BALF), lowered serum IgE, and alleviated lung inflammatory infiltration and pathological damage. It also inhibited lung autophagy and activated the PI3K/Akt/mTOR signaling pathway. In vitro, consistent with in vivo findings, quercetin downregulated proinflammatory factors and autophagy-related proteins in TNF-α/IL-4-stimulated BEAS-2B cells. In addition, the PI3K/Akt/mTOR signaling pathway is also activated by quercetin.ConclusionQuercetin attenuates airway inflammation and lung damage in asthmatic mice. Its therapeutic effect is associated with the modulation of PI3K/Akt/mTOR signaling pathway activity and the regulation of excessive autophagy, which provides new potential approaches and mechanistic insights for asthma treatment.